Workload Analysis at Biro Human Capital to Increase Productivity - Antonia Ratna Hanjani; Moses Laksono Singgih (Institut Teknologi Sepuluh Nopember, 2019)
PT XYZ is a company in Indonesia engaged in manufacturing. One strategy to support these activities is to adjust the workload of the existing work to increase productivity in this company. Workload is very influential on employee performance productivity because the environment and work capacity are aligned with productivity. If the burden received is too heavy, then employee productivity will decrease, whereas if the workload is balanced then employee productivity will increase. Workload Analysis is a method used to determine the time, effort, and resources needed by an organization in identifying the actual needs of Human Resources (HR) in quality and quantity in accordance with the goals and strategies of the organization. Workload analysis with Full-Time Equivalent (FTE) is the allocation of the total number of personnel needed to work on the entire transaction in a system / process at a certain time / period. The staff allocated includes full-time, part-time and short-hour. While the National Aeronautics and Space Administration Administration Task Load Index (NASA-TLX) method is a method used to analyze workers 'mental workload by measuring workers' subjective perceptions. This study will combine both methods to get the expected conclusions. This study aims to measure workload analysis aimed at making the workload between the sections in the Human Capital Bureau to be equally. The calculation results from the FTE stated that the workload contained in the Human Capital Bureau is still not evenly distributed, the recruitment and assessments section has a workload that tends to be low while other parts have a workload that tends to be high. Subjective workload that most affects is on the effort index, which is 24.09%, followed by temporal demand of 21.64%, performance aspects of 21.17%, mental aspects of demand of 19.66%, frustration level of 13, 44%, and the physical demand aspect is 0%